Optimizing MeV photon dose generation in laser-solid interactions via stable beam propagation - A. S. Bogale; L. Yin; S. Palaniyappan; J. Strehlow; S. V. Luedtke; C.-S. Wong; D. Stark; D. C. Gautier; J. C. Fernandez; A. Van Pelt; L. T. Mix; J. Twardowski; et al. (Physical Review Research)
Bremsstrahlung MeV x rays with high doses are essential for radiography of dense objects. Intense, short-pulse laser-driven MeV x-ray sources offer a promising solution, but understanding how the dose scales with laser intensity is crucial for their development. While theory predicts a square root scaling with laser intensity, experimental verification has been hindered by significant shot-to-shot variations, often exacerbated by long preplasma scale lengths from low laser contrast. Here, we demonstrate low shot-to-shot dose variation and confirm the theoretical scaling using high-contrast OMEGA EP laser interactions with millimeter-thick tantalum foils, achieving MeV x-ray doses up to 5.4 rad at 1 m for E_{photon}> 500 keV. Simulations reveal that the unique focal spot of the OMEGA EP laser enables efficient x-ray generation and reduced variability by facilitating deeper laser penetration into dense plasma, even with shorter preplasma scale lengths.